Semiotic interpretation of selected Psalms inscriptions (23, 35, 121) on motor vehicles in Nigeria - Adamo, David T. (Scriptura : Journal for Contextual Hermeneutics in Southern Africa, 2015)
Semiotics is defined as 'thinking in signs' that is, a set of theories and analytical practices concerned with the process of 'production of meaning.' Hence, semiotics is anything that is used to tell or communicate. Semiotic exegesis is the application of semiotic paradigms to critical biblical studies. The path of semiotic analysis as applied to the critical study of the Bible took off in the seventies and the turning points came in the eighties and continued in the nineties into the present. The inscriptions of Psalms 23, 35, and 121, represent the presence of the Almighty God who is believed to be travellers' rescort and that such signs or inscriptions on vehicles sanctify the vehicles against accidents, deaths, armed robberies and kidnappings on many of Nigeria's dangerous roads where no one is actually sure of any safe trip, because these are signs of protection, healing and success.
free